Joachim Schmid works - Schmid, Joachim 1955- (Elisabeth Tonnard, 2016)
Thirty-three photographs of Joachim Schmid working on his E-Book. (E-Book was published in February of 2016 and is based on a letter Joachim wrote to me. The words of this letter remain invisible in his book but every E is included in the form of a photograph. The various E's, almost 500 of them, were photographed in a number of different cities during 2015. There is no digital version of the book.) Joachim Schmid is well-known for his work with other people's photographs. It is less known, or even unknown, that he takes the camera to hand himself sometimes. This little book documents just that and thereby provides a so far unseen aspect of Joachim Schmid's practice. We get a glimpse of the artist's movements in the age of lcd-screens and in addition to that a portrait of the streets that write to us.-- Homepage der Künstlerin (Stand: 03.09.2018): https://elisabethtonnard.com/works/joachim-schmid-works
Keywords: Tonnard, Elisabeth -- 1973-; Künstlerbuch; Bildband